First-time home buyers and residential investment volatility - Jonas Daniel Maurice Fisher; Martin Gervais (Federal Reserve Bank of Chicago, 2007)
Like other macroeconomic variables, residential investment has become much less volatile since the mid-1980s (recent experience notwithstanding.) This paper explores the role of structural change in this decline. Since the the early 1980s there have been many changes in the underlying structure of the economy, including those in the mortgage market which have made it easier to acquire a home. We examine how these changes affect residential investment volatility in a life-cycle model consistent with micro evidence on housing choices. We find that a decline in the rate of household formation, increased delay in marriage, and an increase in the cross-sectional variance of earnings drive the decline in volatility. Our findings provide support for the view that the Great Moderation in aggregate fluctuations is not just due to smaller aggregate shocks, but is driven at least in part by structural change.
Keywords: E22; E32; J11; R21; 330; Business Cycles; Housing; Residential Investment; First-Time Home-Buyers; Great Moderation